Economic impact of people's participation in forest management (a case study of Kabhre Palanchwok, Nepal) (Economic Journal of Development Issues, 2012)
Forests as important renewable natural resources provide direct and indirect benefits to the people. Basically, it provides basic products of timber, poles, fuel wood, twigs, fodder, grass, leaf litter, and non-timber forest products (NTFPs) for the use of construction work, agriculture, livestock keeping, and forest based industries, etc. Similarly, a proper use of forests, forest products, and sustainable management could also contribute to income and employment generation and thereby reduction in the level of poverty of the nation. In addition, forests also provide vital role for bio-diversity conservation, environmental protection and ecological balance of the nation. Historically, people’s participation in forest protection and management work is very old through many informal traditional and indigenous forest management committees. But it has formally and legally been recognized only since mid of 1970’s through various forest plans, policies, acts, regulation and guidelines. The major aims of people’s participation are for basic forest products, socio-economic development, and overall improvement of forest resources in which the government and I/NGOs could also help significantly.DOI: http://dx.doi.org/10.3126/ejdi.v13i0.7218 Economic Journal of Development Issues Vol.13 & 14 2011, pp.139-151